Analyzing verbal and pictorial Arab’s facebook posts during the Israeli attack on Gaza Strip in 2021 - Al-Dala’ien, Othman Aref; Al-Daher, Zeyad; Al-Shboul, Yasser; Al-Rousan, Mohammad (Penerbit Universiti Kebangsaan Malaysia, 2023)
Arab users of social media could express their political views regarding the Palestinian-Israeli conflict between March and June 2021 amid the repressive policies adopted by social networking sites during that period (see e.g., Rayhan-uddin, 2021; Al-Grtly, 2021). In order to evade such policies, Arab users have used some tricks that are worth analysis from a linguistic perspective. The current study analyzes verbal and pictorial Arab’s posts circulated on Facebook during the Israeli attack on Gaza Strip in 2021, and it investigates the attitudes of Facebook Arab users regarding the Palestinian case. The data of the current study consisted of (55) written posts and (47) visual posts collected from the accounts of selected Arab caricaturists and activists. The model of analysis, which was adopted from Kress and van Leeuwen's social semiotic approach, clarifies different messages in visual posts that are categorized according to Kress and van Leeuwen’s representational process types. This study asserts that visual encoding can carry implicit messages that require analysis to uncover the hidden symbolic meanings as well as the interactions between the various signs in caricatures and their ideological and social impacts. The study highlights an ignored part of visual communication in the Arab world and presents novel implications for the domains of semiotics and discourse analysis. Furthermore, this study pursued to provide the field of semiotics with new insights through examining how signs, (e.g., in verbo-pictorial images), can participate in denoting meaning pertinent to the social and political standards of a specific community.